2019
DOI: 10.3389/fmicb.2019.00294
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Structural Diversity of Microbe Secondary Metabolites Using OSMAC Strategy: A Literature Review

Abstract: Microbial secondary metabolites (MSMs) have played and continue to play a highly significant role in the drug discovery and development process. Genetically, MSM chemical structures are biologically synthesized by microbial gene clusters. Recently, however, the speed of new bioactive MSM discovery has been slowing down due to consistent employment of conventional cultivation and isolation procedure. In order to alleviate this challenge, a number of new approaches have been developed. The strategy of one strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
171
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(181 citation statements)
references
References 213 publications
(213 reference statements)
3
171
0
7
Order By: Relevance
“…It has been revealed that fungi possess far more gene clusters encoding secondary metabolites than their characterized compounds (Khaldi et al, 2010). In order to solve this challenge, a number of manipulations have been used to regulate the production of secondary metabolites from fungi, such as One strain many compounds (OSMAC) (Pan et al, 2019), co-culture (Yu et al, 2019), interspecies crosstalk (Wang et al, 2019), and heterologous expression (Huo et al, 2019;Zhang et al, 2019). Among these methods, chemical epigenetic manipulation has been demonstrated to be a promising strategy to wake the silent biosynthetic gene clusters to obtain novel compounds and has been applied to the marine fungi (Asai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that fungi possess far more gene clusters encoding secondary metabolites than their characterized compounds (Khaldi et al, 2010). In order to solve this challenge, a number of manipulations have been used to regulate the production of secondary metabolites from fungi, such as One strain many compounds (OSMAC) (Pan et al, 2019), co-culture (Yu et al, 2019), interspecies crosstalk (Wang et al, 2019), and heterologous expression (Huo et al, 2019;Zhang et al, 2019). Among these methods, chemical epigenetic manipulation has been demonstrated to be a promising strategy to wake the silent biosynthetic gene clusters to obtain novel compounds and has been applied to the marine fungi (Asai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, algae-derived fungi have been reported to be the largest source of secondary metabolites with diversified bioactivities [1,2], and that can be exploited potentially as lead compounds for new drug development. It was reported that by employing one of the post-genomic strategies, one strain many compounds (OSMAC), on the cultivation of the fungal strains could enhance the quantity and diversity of fungal secondary metabolites [3,4]. The OSMAC approach usually involved the manipulation of culturing parameters, such as media formulation, temperature, agitation, luminosity, aeration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…enhance the quantity and diversity of fungal secondary metabolites [3,4]. The OSMAC approach usually involved the manipulation of culturing parameters, such as media formulation, temperature, agitation, luminosity, aeration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, OSMAC (one strain many compounds) [ 13 ] and molecular networking (MN) [ 14 ] approaches were strategically combined to perform a downstream exploration of the diversity of secondary metabolites produced by P. eucrina D2 under different conditions. The metabolome turned out to be very complex and molecular networking analysis allowed the annotation of several metabolites that were clustered in three subgroups: lipoamino acids, diketopiperazines and surfactins.…”
Section: Introductionmentioning
confidence: 99%